2021
DOI: 10.1371/journal.pone.0249659
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis and systematic review of changes in joint position sense and static standing balance in patients with whiplash-associated disorder

Abstract: Objective To synthesise and analyse the current evidence regarding changes in joint position sense (JPS) and standing balance in people with whiplash-associated disorder (WAD) taking the presence or absence of dizziness into account. Data sources PubMed, CINAHL Plus, Web of Science, Embase, MEDLINE and APA PsycINFO were searched by two independent reviewers from inception until August 2020 and reference lists of all included studies were also reviewed. Study selection Only cross-sectional studies that meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
1
17
0
6
Order By: Relevance
“…In addition to kinematic features and strength, higher fear of movement was also associated with poorer proprioception (larger joint position error). However, findings for this relationship, as well as on the clinical utility of sensorimotor tests in people with neck pain, are not consistent across the literature 17 , 45 . In this regard, the structure of a network may reveal the existence of interactions across features able to impact their assessment.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition to kinematic features and strength, higher fear of movement was also associated with poorer proprioception (larger joint position error). However, findings for this relationship, as well as on the clinical utility of sensorimotor tests in people with neck pain, are not consistent across the literature 17 , 45 . In this regard, the structure of a network may reveal the existence of interactions across features able to impact their assessment.…”
Section: Discussionmentioning
confidence: 74%
“…It has been shown that fear of movement mediates the relationships among catastrophizing, pain intensity, and disability in people with neck pain 8 , 9 , yet any interactions with movement avoidance and deconditioning are less clear 10 , 11 . Besides changes in physical activity levels, people with neck pain often present with several specific changes in physical function including reduced range and speed of movement 12 , 13 , altered variability and smoothness of movement 14 , 15 , impaired proprioception 16 , 17 , and reduced neck muscle strength 18 , 19 , which potentially could all be influenced by fear of movement.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was also observed in previous studies of patients with persistent WAD, who have similar pain intensity to the cohort tested in the current study [ 92 , 93 , 94 ]. A recent meta-analysis, found that patients with chronic WAD have significant larger JPE following cervical rotation when compared to healthy controls, but there is a discrepancy between studies [ 16 ]. Such discrepancies could be attributed to various factors.…”
Section: Discussionmentioning
confidence: 99%
“…Altered neuromuscular function is a common feature in patients with acute and CNP including those that have sustained a whiplash injury [ 12 , 13 , 14 ]. These changes include disturbances in muscle strength, muscle behaviour and proprioception [ 15 , 16 , 17 , 18 ]. Additionally, restricted neck range of motion (RoM), as a static measure of movement, has been extensively documented for patients with neck pain of both traumatic and idiopathic origin [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 This includes increased activation of the superficial neck flexors, 17 reduced maximum angular velocity of neck movements, 15,16 and reduced smoothness of neck movement. 16 Moreover, other changes such as increased repositioning error, 18 reduced conjunct motion, 19 and changes in deep neck muscle activation 20 have also been observed in patients with chronic WAD. Of relevance, studies in acute WAD have revealed early changes in motor behavior 17 that may persist even after the acute phase 17,20 suggesting that these factors could play a role in the transition to chronicity.…”
mentioning
confidence: 99%